MODELLING OF POVERTY PERCENTAGE IN EAST JAVA PROVINCE WITH SEMIPARAMETRIC REGRESSION APPROACH - Syahzaqi, Idrus; A., Salman Alfarizi P.; Fithriasari, Kartika (PATTIMURA UNIVERSITY, 2023)
Poverty is an economic problem faced by all countries in the world, including Indonesia. Poverty is seen as the inability of a person from an economic standpoint to meet basic food and non-food needs as measured from the expenditure side. East Java Province is used as the object of research because this province has the highest economic growth in Java Island after DKI Jakarta province in the last 5 years. However, East Java is also included in the province with the highest number of poor people on the island of Java. Several independent variables that are thought to influence the percentage of poverty in East Java are the Open Unemployment Rate (TPT), Life Expectancy Rate (AHH), Average Years of Schooling (RLS), Population Density, and GRDP Rate. Sources of research data come from the East Java BPS website and East Java Open Data. Data analysis was performed using a semiparametric regression approach. The results of the analysis obtained good performance values, namely the MSE value of 12,2156 and the R2 value of 98,71%.